Organizational effectiveness of Ugandan building firms as viewed by craftsmen - Alinaitwe, Henry; Mwakali, Jackson A.; Hansson, Bengt (Journal of Civil Engineering and Management, 2009)
Construction industries, especially those in developing countries, face the problems of low productivity. It comes about partly due to organizational ineffectiveness. The major attributes of organizational effectiveness are identified from literature. Means to achieving greater organization effectiveness and higher productivity are identified under the major headings of cohesion and morale of workers, adaptability, information communication, and planning. Using a structured questionnaire survey on building craftsmen in Uganda, results suggest that most workers are not satisfied with the financial reward, level of status is not able to achieve personal goals. Workers are not satisfied with the level of training. The variables are weak points in organizational effectiveness. In addition, workers are not satisfied with the level of participation in decision‐making. There is a need to dwell on these grey areas in order to improve the organizational effectiveness of building firms, especially in developing countries. Santrauka Dauguma statybos rinkų, ypač besivystančių šalių, susiduria su prasto produktyvumo problema. Menkas produktyvumas iš dalies yra veikiamas organizacinio efektyvumo. Organizacinio efektyvumo pagrindiniai rodikliai yra aptarti literatūroje. Būdai didesniam organizaciniam efektyvumui ir produktyvumui pasiekti nustatomi naudojant kohezijos sąvoką ir darbuotojų moralę, gebėjimą prisitaikyti, informacijos pasikeitimą ir planavimą. Meistrų struktūrinės apklausos Ugandoje rezultatai parodė, kad dauguma darbuotojų nėra patenkinti atlygiu už darbą ir negali pasiekti savo asmeninių tikslų, taip pat ir mokymo lygiu. Šie dalykai yra silpnoji organizacijos vieta. Be to, darbuotojų netenkina dalyvavimo spendimų priėmimo lygis. Todėl reikia apsistoti ties šiais klausimais norint gerinti statybos įmonių organizacinį efektyvumą, ypač besivystančių šalių. First Published Online: 14 Oct 2010 Reikšminiai žodžiai: organizacinis efektyvumas, rodikliai, darbo rinka, produktyvumas, Uganda